Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan PRAMUDI Pada Perum DAMRI Cabang Bandara Soekarno – Hatta - Dela Rosa; Bintang Narpati; Wirawan Widjanarko (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to find out whether compensation and work motivation have a partial and simultaneous effect on job saticfaction of driver employees at Perum Damri Soekarno – Hatta Airport Branch. This research uses quantitative methods to distributing questionnaires. The population of this study consisted of all 100 employees of Perum Damri Soekarno – Hatta Airport Branch. For identification, saturated sampling technique was used as the sampling method. The research results show that the compensation variabel partially has a positive and significant effect on employee job satisfaction. In some cases, fluctuations in work motivation can have a positive and significant impact on employee job satisfaction. And at the same time compensation and work motivation influence the job satisfaction of driver employees at Perum Damri Soekarno – Hatta Airport Branch